2011
DOI: 10.1007/s10903-011-9565-3
|View full text |Cite
|
Sign up to set email alerts
|

Factors Influencing Healthcare Utilization Within a Free Community Clinic

Abstract: The purpose was to explore the relationship between the presence of a free community clinic and factors associated with utilization of healthcare through a secondary data analysis. Using a descriptive correlational design, results were analyzed to explore relationships between potential utilization of healthcare, identification of a regular source of healthcare, and health insurance status. Most subjects would not seek healthcare if the free community clinic was not available. Subjects with health insurance we… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
11
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(11 citation statements)
references
References 21 publications
0
11
0
Order By: Relevance
“…In line with this study finding, Jana & Harata wrote that the rural poor visit the community clinics for treatment because they are provided medicine and treatment free of cost (Jana & Harata, 2016). Besides, migrant poor, less educated, and ethnic minorities are the prime seekers of CC because of face time, transportation, and cost of treatment (Douangmala et al, 2012;O'Malley & Mandelblatt, 2003). The quality of services and equal access to community clinics are mostly affected by both demand and supply-side factors (Hamid et al, 2005).…”
Section: Findings and Discussion Of The Study Challenges Of Access To The Health Care System Of Community Clinics Socio-economic Factorsmentioning
confidence: 68%
“…In line with this study finding, Jana & Harata wrote that the rural poor visit the community clinics for treatment because they are provided medicine and treatment free of cost (Jana & Harata, 2016). Besides, migrant poor, less educated, and ethnic minorities are the prime seekers of CC because of face time, transportation, and cost of treatment (Douangmala et al, 2012;O'Malley & Mandelblatt, 2003). The quality of services and equal access to community clinics are mostly affected by both demand and supply-side factors (Hamid et al, 2005).…”
Section: Findings and Discussion Of The Study Challenges Of Access To The Health Care System Of Community Clinics Socio-economic Factorsmentioning
confidence: 68%
“…They collected the data on participants’ insurance status and access of care, reporting 34.4% of uninsured had no usual source of medical care, 25.8% had no doctor visit in the last year and over 81% reported no specialist visit in the last year [ 6 ]. It is worth-mentioning that lack of primary care can result in increased emergency room use and increased health care costs [ 7 , 8 ].…”
Section: Introductionmentioning
confidence: 99%
“…The United States federal government recognizes the importance of promoting utilization of FQHC by the uninsured and underinsured which is exemplified by the provision in the Patient Protection and Affordable Care Act on improving access to FQHC [ 9 , 10 ]. Several studies have shown that community health centers including FQHCs save the health system millions of dollars partly by reducing unnecessary emergency visits of the uninsured and underinsured [ 7 , 11 ]. Therefore evaluating efficiency of FQHCs patients’ outreach and identifying barriers to their utilization can aid in optimizing access to care in vulnerable communities.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…8 These clinics have been shown to provide costeffective and efficient care matching or exceeding the quality of care provided to insured populations and decreases emergency department visits and hospitalizations. [9][10][11] A promising avenue to supplement free clinics in meeting the challenges of providing care for uninsured patients is to build relationships and promote collaboration between community free clinics and academic health centers.…”
Section: Introductionmentioning
confidence: 99%